2014
DOI: 10.3168/jds.2014-8225
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota characterization of a Belgian protected designation of origin cheese, Herve cheese, using metagenomic analysis

Abstract: Herve cheese is a Belgian soft cheese with a washed rind, and is made from raw or pasteurized milk. The specific microbiota of this cheese has never previously been fully explored and the use of raw or pasteurized milk in addition to starters is assumed to affect the microbiota of the rind and the heart. The aim of the study was to analyze the bacterial microbiota of Herve cheese using classical microbiology and a metagenomic approach based on 16S ribosomal DNA pyrosequencing. Using classical microbiology, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
96
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 130 publications
(104 citation statements)
references
References 48 publications
6
96
0
2
Order By: Relevance
“…While the significance of the presence of these populations is not yet clear, particularly at the levels present in the cheese, they may play a role in ripening (38,49,54). Psychrotrophic bacteria, including Psychrobacter and Pseudomonas, have previously been isolated from a variety of cheeses as well as raw milk and are particularly adapted to lowtemperature milk storage conditions (49,55,56).…”
Section: Figmentioning
confidence: 99%
“…While the significance of the presence of these populations is not yet clear, particularly at the levels present in the cheese, they may play a role in ripening (38,49,54). Psychrotrophic bacteria, including Psychrobacter and Pseudomonas, have previously been isolated from a variety of cheeses as well as raw milk and are particularly adapted to lowtemperature milk storage conditions (49,55,56).…”
Section: Figmentioning
confidence: 99%
“…It could be assumed that these LAB originated from raw milk and the endogenous culture, as they presented high counts of LAB at the time of cheese manufacture, 6.4 log units for raw milk (both seasons) and 7.0 and 8.0 for endogenous culture (rainy and dry seasons, respectively). Delcenserie et al (2014) reported that the average count of LAB in a Belgian protected designation of origin cheese was 7.5 log units when made with raw milk. The ripening time only influenced the mean counts of LAB in the M17 medium during the dry season (Table 1).…”
Section: Microbiological Counts and Basic Characterization Of Isolatesmentioning
confidence: 99%
“…PCR reactions were carried out according to Delcenserie et al (2014) in a final volume of 100 μl containing 5 U of FastStart high-fidelity polymerase (Roche Diagnostics Belgium NV), 1× enzyme reaction buffer, 200 μM of dNTP mix (Eurogentec S.A., Seraing, Belgium), 0.2 μM of each primer, and 100 ng of template DNA. The PCR reactions were performed in a Mastercycler ep gradient apparatus (Eppendorf), with the following program: an initial denaturation for 15 min at 94°C, followed by 25 cycles of denaturation at 95°C for 40 s, annealing at 56°C for 40 s, and extension at 72°C for 1 min, and a final extension step at 72°C for 7 min (Delcenserie et al 2014). PCR products were then run on a 1 % agarose electrophoresis gel, and the DNA fragments were extracted and purified with the Wizard SV PCR purification kit (Promega Corporation, Belgium).…”
Section: Pcr Reactionsmentioning
confidence: 99%